Índice integral para la medición del nivel de servicio de la empresa “TRANSMAYORGA S.A.” del cantón La Concordia - Cárdenas Cagua, Karla Tatiana (2022)
Currently, companies need to be competitive by providing quality. The main purpose of this research was to define a comprehensive index for measuring the level of service of the transport company TRANSMAYORGA S.A. in La Concordia canton, in a way that contributes to effective decision-making; for which, firstly, with the SWOT matrix tool, the current situation in which it is found was diagnosed for the identification of strategies to be implemented, where it was determined that there is a reduced business size, a poorly promoted brand concept, high staff turnover, little investment capacity and poor financial decision making. Next, the components of the processes were identified based on the integral index methodology, determining with the Delphi method, affinity diagram and the participation of expert indicators such as: use of installed capacity, driver productivity, complete deliveries, trips without accidents, deliveries completed on time, percentage of maintenance completed, and operational process that allowed the calculation of the Integral Index through the Saaty method, establishing the respective weighting scales for the indicators and formulating the expression for the measurement of the service level, obtaining the value of the 72,8%, which is equivalent to very good or 5, on a 5-point scale. Demonstrating the reliability and usefulness of the study and recommending for future research to work on the improvement of the proposed procedure, adapting it to the needs of the environment and the processes of the entities where it needs to be applied.